From organized sport motivation to exercise regulations: differences according sport type and intensity. Issue 4 (2nd October 2019) - Lemoyne, Jean; Rivard, Marie-Claude; Girard, Stéphanie; Dubreuil, Pascal
ABSTRACT: Motivation to take part in sufficient levels of physical activity (PA) is a common problem during adolescence. This study investigated associations between motive for sport participation and behavioral regulations towards PA practice. A cohort of 1804 adolescents involved in a large organized sport event, 'Quebec's Summer Games Final' completed questionnaires preceding their participation to the games. Fifteen sports were represented and categorized regarding sport type (team versus individual) and intensity (moderate versus high). Group comparisons were conducted with invariance testing. In summary, motives for competition were significantly associated with identified and intrinsic motivation. Motives for fitness-health were significantly associated with identified motivation, and motives for socialization were significantly associated with external motivation. Significant differences were observed, when comparing the level of intensity and sport type. Such differences are attributed to sport culture and from the participants' selection process. This study suggests stakeholders to consider approaches that will develop self-determined regulations among those who are involved in particularly moderate intensity activities.